Concert and assembly, band folio an intermediate repertoire for the active band - HUMMEL, Herman A. (Rubank Inc., 1950)
Pacific GrandeurnEvent of the DaynPrelude in C MinornWaves of the DanubenOde to MusicnDance of the ApprenticesnGreat gate of KievnCome where my love lies dreamingnChampions on paradenFete triumphal